2002
DOI: 10.1603/0022-0493-95.2.377
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Activity of Catnip (Lamiaceae) Essential Oil Components to the German Cockroach (Blattodea: Blattellidae)

Abstract: The essential oil of catnip, Nepeta cataria L., contains two isomers of nepetalactone, E,Z-and Z,Enepetalactone, and was tested for repellent activity to adult male German cockroaches, Blattella germanica (L.), in a choice-test arena. The two isomers of nepetalactone were purified by using preparative thin-layer chromatography and tested for behavioral activity in the choice-test arena. Significant differences due to concentration were detected by analysis of variance, and the responses were compared by least-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 14 publications
3
50
1
Order By: Relevance
“…This indicates that the chemoreceptors involved in this behavioral response are probably located on the antennae. Similar results were obtained by Peterson et al (2002) when evaluated the behavioral activity of catnip, Nepeta cataria L. (Lamiaceae), essential oil components to the German cockroach. Chirino et al (2001) reported repellent effects of crude extracts from fruits of S. molle in neonate larvae of Cydia pomonella (L.) (Lepidoptera:Tortricidae).…”
Section: Blattella Germanica (L) Is An Important Medicalsupporting
confidence: 80%
“…This indicates that the chemoreceptors involved in this behavioral response are probably located on the antennae. Similar results were obtained by Peterson et al (2002) when evaluated the behavioral activity of catnip, Nepeta cataria L. (Lamiaceae), essential oil components to the German cockroach. Chirino et al (2001) reported repellent effects of crude extracts from fruits of S. molle in neonate larvae of Cydia pomonella (L.) (Lepidoptera:Tortricidae).…”
Section: Blattella Germanica (L) Is An Important Medicalsupporting
confidence: 80%
“…Solanaceous plants, like tomato, often make use of these terpenes for the defense against herbivores (Snyder et al, 1993;Kennedy, 2003). Some terpenes have been shown to exhibit repellent properties to insects (Peterson et al, 2002;Birkett et al, 2004;Terry et al, 2007). These plantproduced semiochemicals can potentially be used as insect repellents of natural origin, thus providing an alternative to the use of pesticides (Peterson and Coats, 2001).…”
mentioning
confidence: 99%
“…In addition to responses to human volatiles, we observed responses to nepetalactone in sbtI1 sensilla. Nepetalactone is the primary component of catnip oil, the vapors of which have been shown to be repellent to a diverse number of insect species, including mosquitoes (Amer and Mehlhorn, 2006a;Eisner, 1964;Peterson and Coats, 2001;Peterson et al, 2002). In behavioral tests, nepetalactone acts as a 'spatial repellent', inhibiting the landing rate of Ae.…”
Section: Discussionmentioning
confidence: 99%